Simulation And Fabrication Of Ge Islands On Si Metal-Semiconductor-Metal Photodetectors - Sarmast, Hadi Mahmodi Sheikh (2010)
In this thesis, experimental fabrication and theoretical simulation of Ge islands Si based metal-semiconductor-metal photodetectors have been reported. Radio frequency sputtering was used to deposit Ge thin films on silicon substrates. This is followed by rapid thermal annealing to form Ge islands. Not only that the annealing produces Ge islands but also wetting layer. The size and density of the islands are greatly influenced by the annealing time.